STRUCTURAL, DIELECTRIC AND MAGNETIC PROPERTIES OF Fe-DOPED SrZrO₃ CERAMICS - Chunhong Tang; Qingchun Wu; Cui Yunkang (Ceramics-Silikáty, 2016)

(untitled)
SrZrO₃-based perovskite oxides have been extensively studied for their outstanding physical characteristics, chemical stability, and mechanical properties. With the recent development of multiferroics, room temperature ferromagnetism is expected to be introduced to ferroelectric or dielectric materials by magnetic ion doping in order to obtain single-phase magnetoelectric or magnetodielectric materials. In this work, SrZrO₃ and SrZr0.9375Fe0.0625O3 ceramics were fabricated by a conventional solid-state reaction method. Their structural, dielectric and magnetic properties were carefully investigated. It was found that Fe-doping could effectively improve the dielectric constant of SrZrO₃. Moreover, ferromagnetism with a Curie temperature of about 685 K was successfully introduced by a small amount of Fe dopant. The saturation magnetization and coercive field of SrZrO₃ and SrZr0.9375Fe0.0625O3 ceramics were 3.0 emu/g and 1.3 kOe, respectively, at room temperature. The origin and mechanism of ferromagnetism introduced by Fe dopant is discussed based on the valence fluctuation of Fe ions.